2008
DOI: 10.1111/j.1365-2524.2008.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking at the time of stroke: stroke survivors’ perspectives on their decisions

Abstract: Stroke is a major cause of death and disability in many countries. Early access to the most appropriate medical treatment can improve health outcomes. Despite this, only 30-60% of people who experience a stroke seek medical help within the recommended 3-hour timeframe. This study used open-ended interviews to explore patients' views on factors that influenced their decision to seek help at the time of stroke. Twenty participants were recruited from five centres: three hospitals, a community-based stroke suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 23 publications
(28 reference statements)
5
51
0
Order By: Relevance
“…Therefore, they decided to ignore or, in the best-case scenario, to postpone seeking health care until finishing their work-related commitments. These findings were supported by a study where participants described prioritizing routine responsibilities over their own health needs when making decisions of how to react to their sudden unexplained symptoms (Moloczij et al, 2008).Urging of a Valued Individual was captured in the study participants' narratives as a careseeking factor. Having someone; a spouse, friend, neighbor, or individual whose opinion was valued, such as a nurse, with the individual experiencing stroke symptoms reflected positively in pushing them toward seeking immediate medical attention.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Therefore, they decided to ignore or, in the best-case scenario, to postpone seeking health care until finishing their work-related commitments. These findings were supported by a study where participants described prioritizing routine responsibilities over their own health needs when making decisions of how to react to their sudden unexplained symptoms (Moloczij et al, 2008).Urging of a Valued Individual was captured in the study participants' narratives as a careseeking factor. Having someone; a spouse, friend, neighbor, or individual whose opinion was valued, such as a nurse, with the individual experiencing stroke symptoms reflected positively in pushing them toward seeking immediate medical attention.…”
Section: Discussionmentioning
confidence: 56%
“…Failure to recognize stroke warning signs by individuals, families, or observers may result in delays in receiving life-saving management within this timeframe (Fugate & Rabinstein, 2014). In previous research, the percentage of individuals presenting to a specialize stroke center within 180 minutes of the onset of stroke warning signs was estimated to be 30% to 60% (Moloczij, McPherson, Smith & Kayes, 2008). This indicates that at least 40% of individuals experiencing stroke symptoms fail to access health services within the recommended timeframe (Moloczij et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The help-seeking patterns of different individuals have been shown to be complex. Interview-and population-based studies report that the decision to seek help was affected by symptom severity, living alone, knowledge of stroke, fear of the consequences of stroke, previous negative experience on hospitals, perceptions of the remit of medical services, belonging to an ethnic minority, presence of bystanders and involving a friend or relative in the decision of contacting medical services (Moloczij et al 2008, Mackintosh et al 2012. Better stroke knowledge has not been necessarily associated with correct stroke response behaviour or the decision to call the emergency telephone number (Schroeder et al 2000) of the symptoms have been suggested to play an important role in the help-seeking process (Rosamond et al 1998, Schroeder et al 2000, Iguchi et al 2006.…”
Section: The Emergency Telephone Call and Ems System Activationmentioning
confidence: 99%
“…A knowledge deficit can in turn significantly influence symptom appraisal, and symptom appraisal that is not interpreted as serious and alarming can lead to delays in seeking help (Howell et al, 2008;Mason & Strauss, 2004a;Moloczij, McPherson, Smith, & Kayes, 2008).…”
Section: Knowledge Of Lung Cancermentioning
confidence: 99%